2021
DOI: 10.1111/joca.12350
|View full text |Cite
|
Sign up to set email alerts
|

Impact of consumer animosity, boycott participation, boycott motivation, and product judgment on purchase readiness or aversion of Kurdish consumers in Iraq

Abstract: This study aims to investigate the impact of Turkish–Kurdish political relations on Kurdish consumers' behavior toward Turkish products. The following variables were included as predictors: consumer animosity, boycott participation, boycott motivation, and product judgment. An online survey was conducted to collect the data; it attracted 1,100 participants. Seven hypotheses were tested using descriptive statistics, correlation coefficients, and structural equation modeling. The study findings show that consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 55 publications
1
22
1
2
Order By: Relevance
“…The systematization of scientific publications made it possible to single out several studies that play a fundamental role in the development of e-commerce and online shopping behavior theories. Some scientists concluded that motivation, environment, political factors [12,13], accessibility, and communication [14] have a substantial influence on the attitude of online consumers to e-services. Other scholars have devoted themselves to consumer trust and its effect on online shopping behavior [15,16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The systematization of scientific publications made it possible to single out several studies that play a fundamental role in the development of e-commerce and online shopping behavior theories. Some scientists concluded that motivation, environment, political factors [12,13], accessibility, and communication [14] have a substantial influence on the attitude of online consumers to e-services. Other scholars have devoted themselves to consumer trust and its effect on online shopping behavior [15,16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Cronbach's Alpha for ten employee engagement's ten items = .849 which is greater than .6 this means that ten items used for employee engagement factor were reliable for this study and the Cronbach's Alpha for ten corporate social responsibility's ten items = .775 which is greater than .6 this means that ten items used for corporate social responsibility factor were reliable for this study. The above table (3) shows the correlation analysis between employee engagement and corporate social responsibility. The value of Pearson Correlation = .858 ** which is greater than 0.01 this means that there is a positive and strong correlation between employee engagement and corporate social responsibility.…”
Section: Methodsmentioning
confidence: 99%
“…The research model was created to reveal the relationships between the variables in line with the literature. Models and hypotheses were created within the scope of the research; Klein and John (2001), Tian (2010), Antonetti et al (2019), Ali (2021), Öztürk and Nart (2021). Figure 1 shows the research model.…”
Section: Research Model and Scalesmentioning
confidence: 99%
“…As a result, a boycott represents antimass consumer behaviour towards a product, brand, business, country, or idea, influenced by some political and social external environmental factors. Consumer boycott behaviour can be affected by many factors such as animosity, negative WOM, religion, ethnocentrism, and country of origin image (Tabassi et al, 2012;Abdul-Talib et al, 2016;Dessy et al, 2017;Ali, 2021).…”
Section: Introductionmentioning
confidence: 99%